2011
DOI: 10.1098/rspb.2011.1778
|View full text |Cite
|
Sign up to set email alerts
|

What causes intraspecific variation in resting metabolic rate and what are its ecological consequences?

Abstract: Individual differences in the energy cost of self-maintenance (resting metabolic rate, RMR) are substantial and the focus of an emerging research area. These differences may influence fitness because selfmaintenance is considered as a life-history component along with growth and reproduction. In this review, we ask why do some individuals have two to three times the 'maintenance costs' of conspecifics, and what are the fitness consequences? Using evidence from a range of species, we demonstrate that diverse fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
789
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 580 publications
(848 citation statements)
references
References 90 publications
20
789
4
1
Order By: Relevance
“…However, they may also benefit from a lower production of reactive oxygen species (ROS; Salin et al 2015b). Such a physiological trade-off between ATP and ROS may help explain the persistence of variation in metabolic rates among individuals; metabolic phenotypes can have differential effects on fitness (Burton et al 2011;Salin et al 2015a). For example, we have shown that individual brown trout with relatively higher SMR perform worse under conditions of low food availability, which may be explained by a reduced capacity to generate ATP above baseline energetic needs (Auer et al 2015c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they may also benefit from a lower production of reactive oxygen species (ROS; Salin et al 2015b). Such a physiological trade-off between ATP and ROS may help explain the persistence of variation in metabolic rates among individuals; metabolic phenotypes can have differential effects on fitness (Burton et al 2011;Salin et al 2015a). For example, we have shown that individual brown trout with relatively higher SMR perform worse under conditions of low food availability, which may be explained by a reduced capacity to generate ATP above baseline energetic needs (Auer et al 2015c).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, AS may have a significant impact on fitness but displays significant intraspecific variation (Farrell et al 2008;Sandblom et al 2014;Auer et al 2015aAuer et al , 2015c; but see Norin et al 2014). Both minimum and maximum metabolic rate are responsible for intraspecific variation in AS since they exhibit consistent differences among individuals over extended periods of time, even within a population under standardized conditions Burton et al 2011;Swanson et al 2012;Careau et al 2014aCareau et al , 2014bGifford et al 2014). In turn, the use of a single metric such as AS conceals a great deal of variation, since individuals with the same AS can have markedly different absolute levels of minimum and maximum metabolic rate (Auer et al 2015c).…”
Section: Introductionmentioning
confidence: 99%
“…The low metabolic rate of M-slow snakes at 207C may represent a mechanism to conserve energy when temperatures are low and resources are unavailable (Aleksiuk 1971(Aleksiuk , 1976Burton et al 2011). A low metabolism would allow Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies controlling for resource availability have found both negative (e.g., Danzmann et al 1987) and positive (e.g., Hoogenboom et al 2012) relationships between growth and metabolic rate (reviewed in Glazier 2015). Taken together, these studies indicate that a single optimal metabolic rate may not exist and that fluctuations in resource availability may maintain metabolic polymorphisms within populations (Burton et al 2011;Reid et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation